Effect of exercise intervention on anxiety among college students: a meta-analysis - Chen, Peng; Mazalan, Nur Shakila; Koh, Denise; Gu, Yusha (Frontiers in Psychology, 2025)
ObjectiveThis study conducted a meta-analysis to examine the impact of exercise interventions on anxiety levels among college students.MethodsUnder Review Manager 5.3 and Stata17.0, subgroup analyses were conducted on data from 514 subjects across 10 studies from Chinese and English literature. The analyses examined intervention content, intervention period, single intervention duration and intervention frequency. A random effects model was employed to assess the overall effect size and heterogeneity.ResultsThe exercise intervention demonstrated a significant effect on reducing anxiety among college students, with a large effect size (d = −0.83). The heterogeneity test of intervention content (I2 = 0%) revealed high consistency in the specific content of exercise intervention across studies. However, substantial heterogeneity was observed in single intervention time (I2 = 75%), intervention frequency (I2 = 75%), and intervention period (I2 = 72%), indicating significant variations across studies. These differences suggest that varying durations, frequencies, and periods of intervention yielded different effects on college students’ anxiety levels.ConclusionThis meta-analysis has found that structured physical exercise programs, especially mind–body integrative exercises, can alleviate anxiety to the greatest extent, offering evidence-based guidance for implementing targeted exercise interventions in college mental health programs.Systematic review registrationhttps://doi.org/10.37766/inplasy2024.11.0006.